Viability and control of Fusarium graminearum in barley seeds Viabilidade e controle de fusarium graminearum em sementes de cevada - Agostinetto L. (2018)
© 2018, Universidade Estadual Paulista (UNESP). All rights reserved.The aims of this study were to quantify the viability of Fusarium graminearum in barley seeds stored during the inter-harvest period and to verify the effectiveness of the chemical treatment of seeds on the fungus control and on the emerged plant population. The viability of F. graminearum was determined every 35 days, during 10 months of storage, for 50 samples of barley seeds of cultivars MN 743, MN 6021, BRS Cauê, BRS Brau and BRS Elis. Samples of 1 Kg seeds were treated with the mixture of fungicides and insecticides: 1) triadimenol + iprodione + imidacloprid; 2) (carboxin+thiram) + iprodione + carbendazim + thiamethoxam; 3) (carboxin+thiram) + difenoconazole + carbendazim + thiamethoxam; 4) difenoconazole + iprodione + carbendazim + thiamethoxam, and subsequently plated in potato dextrose agar culture medium (PDA), stored during 10 days in a growth chamber and assessed by optical microscopy. Treated seeds were sown in the field in 5.0 m X 1.0 m experimental plots arranged in completely randomized block design with four replicates. The emerged plant population was quantified at 21, 28 and 35 days after sowing on the four central lines of each experimental plot. The fungus was detected in all cultivars, showing a significant negative reduction in its viability as the storage period increased. After 10 months of storage, the mean incidence of the fungus was 2%, which can ensure inoculum for transmission. Seed treatments with the presence of the active ingredient carbendazim provided F. graminearum control superior to 90% and allowed a larger population of emerged plants.